WAWASAN FILOSOFIS TENTANG DISTRIBUSI KEKAYAAN DALAM PERSPEKTIF FILSAFAT EKONOMI ISLAM - Nurul Syafriani; Ratih Silviany; Lira Amelia; Ahmad Wahyudi Zein (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the distribution of wealth in the perspective of Islamic economic philosophy with a focus on the importance of social justice, moral responsibility, and solidarity in the management of economic resources. In Islam, the distribution of wealth is seen not only as an economic process, but also as an implementation of the ethical values of Islamic economics through instruments such as zakat, infaq, and waqf that ensure the distribution of wealth. This study uses a qualitative approach with library research methods to analyze various relevant literature, with three main focuses: epistemology, ontology, and axiology of wealth distribution in Islamic economics. Based on an analysis of 16 journal articles published between 2017-2024, this study concludes that the distribution of wealth in Islamic economics emphasizes the principles of justice, shared welfare, and fair management of resources. The distribution system in Islamic economics aims to reduce socio-economic inequality, by integrating moral, social, and spiritual values, and offering a fairer and more sustainable alternative compared to the capitalist or Marxist economic system.